Practical Teaching of Processor Design According to a Project-Based Teaching-Learning Methodology at the School of Engineering of UFMG - Duarte, Ricardo de Oliveira; Donoso-Garcia, Pedro Francisco (International Journal of Computer Architecture Education, 2012)
This article describes in detail the development of didactic material for the practical teaching-learning of Computer Organization and Architecture in undergraduate engineering courses, focusing on equipping students for processor design. Based on a processor design sequence presented to the student in specifically developed didactic material, a proposal is constructed for laboratory activities in which the student is challenged to develop a processor from a document containing a minimal set of requirements. Students make design decisions and present their own solutions, rather than simply repeating predetermined tasks commonly found in traditional laboratory teaching methodologies based on class guides. The principle of the teaching-learning methodology, which we call project-oriented, is presented in this article, as well as the considerations in developing the didactic material. This methodology has been applied in a theoretical and practical course known as Systems, Processors, and Peripherals, which is mandatory for three engineering undergraduate courses at the Federal University of Minas Gerais (UFMG). The observed results include increased motivation, improved learning and participation of students in classes and proposed activities, and a reduction in dropout and failure rates.